Central composite design (CCD) optimization of phytohormones supplementation for enhanced cyanobacterial biodiesel production. (January 2019) - Anahas, Antonyraj Matharasi Perianaika; Muralitharan, Gangatharan
Abstract: Based on our previous findings, two potent cyanobacterial strains namely, Anabaena sphaerica MBDU 105 and Nostoc calcicola MBDU 602 showed suitability for biodiesel production were chosen in this study to enhance biomass and lipid accumulation. The present study investigated the effect of nutrient supplementation with different carbons sources, chemical modulators and nutrient starvation on lipid accumulation. Nutrient supplementation with organic carbon sources yielded higher biomass (5.38–7.96 fold) and lipid productivity (2.81–2.19 fold) rather than lipid content. For chemical modulators, indole-3-carboxaldehyde (I3C) and kinetin (KT) increased lipid accumulation by 22 ± 1.9 and 34 ± 1 (% dwt), respectively. Therefore, central composite design was performed to assess the interactive effect of I3C and KT on lipid content, biomass and lipid productivity, fatty acid composition and their fuel properties. To the best of our knowledge, this is the first report demonstrating that I3C promote the biomass and lipid productivity of tested heterocystous cyanobacterial strains. Highlights: Influence of phytohormones I3C and KT on biomass and lipid productivity was investigated. I3C and KT enhanced the lipid content of Anabaena sphaerica MBDU 105. Media optimization using RSM increased the lipid productivity of tested cyanobacterial strains. Biodiesel quality parameters were evaluated from FAME profiles. Economic feasibility analysis of using the phytohormones for mass production was estimated.